Methotrexate in sarcoidosis: hematologic and hepatic toxicity encountered in a large cohort over a six year period - Baughman, Robert P.; Cremers, Johanna; Harmon, Martina; Lower, Elyse; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
ABSTRACT. Background: Methotrexate (MTX) is a second line agent for treatment of sarcoidosis. Its long term safety and efficacy in sarcoidosis remains unclear. Methods: This was a retrospective review of patients seen at the University of Cincinnati Sarcoidosis Clinic over a six year period. For each visit, complete blood count, liver function testing, and dosing and outcome of MTX was noted. For efficacy, we compared the outcome of therapy of patients treated with either MTX or infliximab for one year and results scored as improved, stable, or worse.Results: Over six years, 1606 sarcoidosis patients were seen with a total of 13,576 clinical visits. During the study period, 607 patients (38% of total) were receiving MTX and had available blood work. Moderate elevation of alanine aminotransferase (ALT) (>3 time upper limit normal) was seen in nine (1.6%) patients. White blood count of